Surface Characteristics of Poly(alkyl methacrylate)s from Molecular Dynamics Simulations Using All‐Atom Force Field. Issue 12 (16th December 2021) - Lee, Sanghun; Jeong, Wonhee; Frank, Curtis W.; Yoon, Do Y.
Abstract: Molecular dynamics (MD) simulations of melt films of poly(alkyl methacrylate)s (PAMAs) with methyl, ethyl, and n ‐butyl substituents, respectively, have been performed using an all‐atom model to investigate their surface and thin film properties. The applied all‐atom force fields predict the bulk densities of PAMAs in good agreement with experiments. Moreover, predictions of the surface tensions of PMMA, PEMA, and P n ‐BMA melts are in reasonably good agreement with experiments. The density profiles and orientational‐order parameters of chain segments show atomic‐scale characteristics in the air/polymer interfacial region. In the surface region, the backbone segments of PAMAs form a well‐defined layer structure with the chain vectors oriented parallel to the surface, while the ester side‐chains strongly segregate to the surface region and show perpendicular orientation to the surface, with the most pronounced surface segregation noted for P n ‐BMA. Such surface segregations of chain segments make it difficult to apply a simple relationship between the cohesive energy density and the surface tension of polymers, for example, and should be taken into account in relating the surface/thin film characteristics to the bulk properties of polymers in general. Abstract : The surface tension and the segregation/orientation of chain segments of poly(methyl methachrylate), poly(ethyl metachralte), and poly ( n ‐butyl methacrylate) melting in the air/polymer interface are calculated from atomistic molecular dynamics simulations with all‐atom force fields, in good agreement with experiments.